Manajemen Pemberian Pakan Pada Pembesaran Ikan Kakap Putih (Lates Calcarifer) di UD Marlisdin Desa Suka Jaya Kabupaten Simeulue - Nelvia Mai Susanti; Roslimah Roslimah; Mira Rahmita Sari; Rahmat Tillah; Destriman Laoli (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
This study aimed to evaluate the effect of three feeding methods-manual, automatic, and sensor-based-on the growth and feed efficiency of White Snapper (Lates calcarifer). The research was conducted from April to July 2024 in fish farming ponds in North Nias. The research method used was a field experiment with a complete randomized design (CRD) which was analyzed using ANOVA test to compare the significant effects of each feeding method. The results showed that the sensor-based feeding method produced the highest average fish weight growth (3.85 g/day) with the best feed conversion efficiency (FCR) (1.25), significantly superior to the manual and automatic methods (p < 0.05). The sensor-based method proved to be more efficient in meeting fish feed requirements precisely, improving feed efficiency and reducing operational costs. Based on these results, the use of sensor-based technology in the feeding system is recommended as an innovative solution to improve the productivity and sustainability of White Snapper aquaculture.